2015
DOI: 10.1039/c5cc03665h
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced oligomerization of alanine at 25 °C

Abstract: Pressure-induced oligomerization was found from high-pressure experiments at 25 °C on alanine powder soaked in its saturated aqueous solution. The oligomerization to alanylalanine occurred at 5 GPa. The maximum yields of alanylalanine and trialanine were, respectively, 1.1 × 10(-3) and 1.3 × 10(-4) at 11 GPa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…The similar oligomer formation mechanism was found for alanine at pressures 9–11 GPa and 300 K, where alanylalanine and trialanine were formed via alanine dehydration and C-N bond formation 29 . Although we found PAH oligomerization at 3.5 GPa and 500–773 K, the average intermolecular distances of experimental products should be longer than that at a reaction threshold, because the diffraction patterns (and crystal structures) of these hydrocarbons do not undergo significant changes at selected parameters 20 .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The similar oligomer formation mechanism was found for alanine at pressures 9–11 GPa and 300 K, where alanylalanine and trialanine were formed via alanine dehydration and C-N bond formation 29 . Although we found PAH oligomerization at 3.5 GPa and 500–773 K, the average intermolecular distances of experimental products should be longer than that at a reaction threshold, because the diffraction patterns (and crystal structures) of these hydrocarbons do not undergo significant changes at selected parameters 20 .…”
Section: Resultssupporting
confidence: 71%
“…It was emphasized in the previous studies that the formation of oligomers simultaneously at high pressures and high temperatures was promoted by energetically activating hydrocarbons under influence of catalysts – copper or platinum 18 , 61 . However in present study and in previous studies 23 , 29 oligomerization of organic compounds was observed at high pressures without any active catalyst.
Figure 6 PAHs oligomerization and carbonization mechanism at high pressure and temperature.
…”
Section: Resultscontrasting
confidence: 63%
“…[1][2][3][4][5][6][7][8] High pressures can substantially alter intermolecular interactions of organic molecules resulting in pressure-induced structural changes and chemical reactions including poly-and oligomerization. 2,3,5,7,9,10 For instance, extreme conditions realized during cometary or meteor impacts are thought to facilitate the chemistry needed to produce polypeptides and other biologically relevant molecules from simple precursors. 7,11,12 Understanding the room temperature structural behavior and equa-tion of state (EOS) for glycine under static compression is a critical step for clarifying the role of elevated thermodynamic conditions on the possible formation of polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Recently, the pressure-induced oligomerization of L-alanine at room temperature was reported. 25,26 The oligomerization might occur partially when distances between the neighboring L-alanine molecules decrease with increasing pressure and finally approaches the reaction threshold. 25 However, the detailed mechanism of the oligomerization has not been revealed.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The oligomerization might occur partially when distances between the neighboring L-alanine molecules decrease with increasing pressure and finally approaches the reaction threshold. 25 However, the detailed mechanism of the oligomerization has not been revealed. Investigation of the effects of pressure on the intermolecular interactions in amino acid crystals may provide essential a) Author to whom correspondence should be addressed: shinozaki.aya@ sci.hokudai.ac.jp.…”
Section: Introductionmentioning
confidence: 99%